The search for optimal nocturnal diurnal heart rate Index targets in ICU patients: a retrospective observational study from large ICU database - Gao, Lan; Shi, QinDong; Zhang, XiaoYu; Bu, Xiang; Zheng, PeiYing; Zhou, LinJing; Yan, JinQi; Li, Hao; Tian, Gang (Frontiers in Cardiovascular Medicine, 2024)
Background: Circadian rhythms play a crucial role in cardiovascular health, with the nocturnal diurnal heart rate index (NDHRI) reflecting significant circadian variations. However, the optimal NDHRI target in Intensive Care Unit (ICU) patients remains undefined. This study aims to establish an evidence-based NDHRI target range and assess its association with mortality. Methods: Data from the eICU Collaborative Research Database (n=32,412) were analyzed. NDHRI was calculated by dividing cumulative nighttime heart rate area by daytime area. Generalized additive models (GAMs) explored the non-linear relationship between mean NDHRI and mortality, adjusting for confounders. Subgroup analyses were conducted based on ethnicity, ICU type, and comorbidities. Results: A U-shaped association was observed between hospital mortality and mean NDHRI (P<0.001). The optimal NDHRI range (40.0%-45.0%) demonstrated the lowest mortality rates. The duration spent within this range correlated inversely with mortality (P<0.001). Subgroup analyses consistently supported these findings across diverse patient profiles. Conclusions: Our findings suggest an association between maintaining NDHRI within the 40.0%-45.0% range and lower mortality rates in critically ill patients, highlighting the potential utility of monitoring circadian heart rate variations in the ICU. Further research and future randomized controlled trials are essential to confirm causality and should consider this NDHRI range as a pivotal reference target.